Managing Opportunities and Challenges of Co-Authorship. (February 2015) - Conn, Vicki S.; Ward, Sandra; Herrick, Linda; Topp, Robert; Alexander, Gregory L.; Anderson, Cindy M.; Smith, Carol E.; Benefield, Lazelle E.; Given, Barbara; Titler, Marita; Larson, Janet L.; Fahrenwald, Nancy L.; et al.
Research with the largest impact on practice and science is often conducted by teams with diverse substantive, clinical, and methodological expertise. Team and interdisciplinary research has created authorship groups with varied expertise and expectations. Co-authorship among team members presents many opportunities and challenges. Intentional planning, clear expectations, sensitivity to differing disciplinary perspectives, attention to power differentials, effective communication, timelines, attention to published guidelines, and documentation of progress will contribute to successful co-authorship. Both novice and seasoned authors will find the strategies identified by the Western Journal of Nursing Research Editorial Board useful for building positive co-authorship experiences.